Changes in historical and future precipitation patterns across the contiguous United States - Sharif, Ridwana Binte; Maggioni, Viviana; Dollan, Ishrat Jahan (Frontiers in Earth Science, 2025)
As anthropogenic climate signals have intensified, precipitation patterns have changed over the contiguous United States (CONUS) and may continue to change in the future. Comparing historical climate model simulations to ground-based observations can help us quantify uncertainties in climate models when simulating precipitation and its changes. This work evaluates precipitation simulated by the Community Earth System Model Version 2 large ensemble (CESM2-LE) against observations from the National Oceanic and Atmospheric Administration Climate Prediction Center Unified CONUS (CPC) during 1948–2022. Next, past precipitation patterns from CPC are compared to future projections (2023–2100) of CESM2-LE for a medium-to-high emission scenario (Shared Socioeconomic Pathways, SSP3-7.0) from a 70-member ensemble. A pixel-by-pixel bias correction is then conducted to remove systemic errors between the model and observations. Results indicate that precipitation variability is drastically reduced in the ensemble mean and suggest caution when using it to draw conclusions regarding precipitation changes. CESM2-LE is shown to underestimate (overestimate) ground observations over CONUS in summer (winter) during 1948–2022. Climate model simulations struggle particularly to capture high-magnitude precipitation (i.e., annual averages larger than 10 mm/day), especially in the Northwestern US. Historical precipitation data show slightly upward patterns in annual, spring, fall, and winter averages, patterns that are projected to continue in the future. Future annual precipitation will increase with respect to historical observations by as much as 11% and 15% in the Northeast and Southeast US (which are already wet regions), respectively, whereas the arid Northern Great Plains region will experience a 15% decrease. Overall results indicate drier summers and wetter winters in the future with respect to the past. Furthermore, the 75th and 95th percentiles of seasonal precipitation will become more extreme during winter by as much as 100% but will decrease during summer by as much as 80%. This study places a strong emphasis on understanding reliable future climate projections, which can be useful when designing community-driven adaptation and mitigation plans for climate change.